Translator’s visibility in mediating confrontational responses of “challenge” strategy at China’s diplomatic press conferences - Yang, Wei; Mansor, Nor Shahila; Ang, Lay Hoon; Yang, Mingxing (Academy Publication, 2024)
The study aims to unveil how translators deal with confrontational responses through their visibility in translating the diplomatic discourse of China’s diplomatic press conferences. Distinct from past theoretical frameworks, this study is grounded in the impoliteness strategies model (Bousfield, 2008) and the concept of translator’s visibility. The corpus focuses on the English-translated responses using the “challenge” strategy, delivered by the spokesperson Hua Chunying throughout 2020. Findings show that the translator’s visibility is mainly presented at the syntactical and lexical levels, and the discursive level is hardly found. The translation strategy of modulation is used most in syntax and reduction most in lexicon. Additionally, the translator’s visibility by using translation strategies can mediate the degree of confrontation. In maintaining the confrontational tone, the main strategies involve modulation in syntax and reduction in lexicon. Linguistic compression and reduction are employed more commonly in weakening the confrontational implication in lexicon, and reduction in syntax. Linguistic amplification is observed more frequently in the lexicon and modulation is more often used in syntax in strengthening the confrontation. This research sheds light on the dynamic interplay between impoliteness strategies and the translator’s visibility, contributing to a deeper understanding of the translator’s engagement in institutional discourse.